Event-Driven Changes in Volatility Connectedness in Global Forex Markets - Peter Albrecht; Evžen Kočenda (CESifo GmbH, 2025)
Using novel methods, we comprehensively analyze volatility connectedness among most traded currencies using high-frequency data from 2009 to 2023. Our study presents the first empirical evidence of a statistically significant association between increases in connectedness and endogenously selected impactful events for most traded currencies. Moreover, we uncover the previously unexplored relationship between twenty-three events affecting global forex connectedness up to one business month ahead and further analyze pre-event connectedness changes. We also distinguish between the transitory and permanent impacts of events on connectedness and confirm the association of four events with a permanent shift in connectedness; two events are associated with the EU and US debt crises. We compute the portfolio weights and hedge ratios for portfolio optimization and uncover the Swiss franc and Japanese yen as the most suitable tools for managing currency risk. The effects of intra-day currency depreciation versus appreciation against the U.S. dollar differ significantly, but the extent of asymmetries declines over time.
Keywords: C58; F31; F65; G01; G15; 330; volatility connectedness; global currencies; bootstrap-after-bootstrap procedure; transitory and permanent effects; debt crisis; portfolio composition and hedging; uncertainty